The ideology of resistance in Sahar Khalifeh's wild thorns - Salameh, Saqer
The study presents an examination of the novel Wild Thorns as a specimen of Palestinian ideological resistance literature. The author, Sahar Khalifeh, engaged in her nation's holy struggle against the Israeli occupation. The novel represents a response to specific dilemmas in Palestine at the time and showcases different types of resistance against the hegemony of the colonizer. The study focuses on the different sources of Palestinian citizens' resistance set against the elements of resistance displayed by the novel's characters. The text was analysed using thematic analysis approach based on Braun and Clarke'S model. Relevant codes were combined into categories which were later synthesized and presented thematically. An inter coder was also used in the analysis process to ensure the trustworthiness of the study. The findings of the study are twofold. Firstly, they reveal that the causes of resistance in Palestine resulted from the harsh living conditions enforced by Israel, as well as the social, political, and psychological dilemmas inherent in those conditions which energized the continuation of the resistance. Secondly, the study finds that certain elements of resistance namely, resilience, displacement, and identity preservation which are captured in the characters' behaviours were followed in order to remind Palestinians of the necessity of resistance as well as to assert their stolen rights. Khalifeh has successfully portrayed the sources of resistance and the characters' behaviour to reflect the reality in Palestine which is made problematic by lsreali occupation. This study argues that violent resistance by the Palestinian is not only a way to resist, but also a tool to express the Palestinian right and a reminder of their cause since Israel restricts the will of the Palestinian people to resist.